Pembelajaran Berbasis Deep Learning: Sebuah Kajian Literatur Sistematis - Latifa Naim, Charisha; Rahmi, Fitri Olvia (LP2M UIN Ambon, 2025)
Twenty-first-century learning requires instructional approaches that promote deep understanding and active student engagement. Pedagogical deep learning emphasizes mindful, meaningful, and joyful learning. This study aims to systematically review the implementation of pedagogical deep learning in educational practices. A Systematic Literature Review was conducted by analyzing ten relevant research articles. The findings indicate that deep learning-based instruction enhances student engagement, conceptual understanding, higher-order thinking skills, and learning motivation. However, its effectiveness depends on teacher readiness and instructional design. Overall, pedagogical deep learning shows strong potential as an effective instructional approach when implemented in a planned and contextual manner.